Natural vaccines accumulated in face masks during COVID-19: Underappreciated role of facial masking - Nilesh Kumar Sharma; Sachin Sarode; Gargi Sarode (Elsevier, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a causal agent behind coronavirus disease 2019 (COVID-19). Despite promising developments in therapeutic and preventive avenues, the importance of facial masking is a key factor for the protective measures among exposed human populations. Preclinical and clinical data on the importance of facial masking concerning asymptomatic over symptomatic COVID-19 cases is limited. The recent introduction of the concept of SARS-CoV-2 associated molecular particle patterns (SAMPPs) as a natural vaccine has opened new avenues for the comprehensive development of immunity. To take this further, the scope of natural vaccines accumulated in facemasks during facial masking needs to be highlighted that may directly or indirectly contribute to building adaptive immunity among human populations. This paper attempts to discuss the underappreciated contributions of facial masking in the management of COVID-19 at the global level.